Ubuntu: the old and the neo - Flatela, Sinovuyo (Stellenbosch : Stellenbosch University, 2025)
Flatela, Sinovuyo. 2025.Ubuntu: the old and the neo. Unpublished masters thesis. Stellenbosch: Stellenbosch University [online]. Available: https://scholar.sun.ac.za/handle/10019.1/132355